Damned land: concentration camps for the drought poor - Rios, Kênia Sousa; Júnior, Edmilson Alves Maia (Em Perspectiva, 2020)
The lecture "Convicts of the land: concentration camps for the poor of the drought", with Profa. Kênia Sousa Rios (UFC), is an activity carried out in conjunction with Em Perspectiva, the History course at FECLESC-UECE and the Vale do Acaraú State University, with the Postgraduate Program in History at the Federal University of Ceará and the Interdisciplinary Master in History and Letters from FECLESC-UECE.